Kualitas Layanan Rawat Gabung dengan Tingkat Kepuasan Keluarga di Kamar Bayi Sehat - Ani Kurniasari; Irawan Danismaya; Egi Mulyadi; Azhar Zulkarnain Alamsyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the relationship between the quality of outpatient care services and family satisfaction levels, providing a basis for hospitals to improve service quality. The research method used was a quantitative cross-sectional approach. Purposive sampling was used with 60 respondents. The results showed a p-value of 0.010, meaning p<0.050. The majority of respondents (93.3%) rated the quality of outpatient care services as high quality, and the majority (93.3%) were satisfied with the outpatient care they received. In conclusion, there is a relationship between the quality of outpatient care services and family satisfaction levels at the Healthy Baby Room. Keywords: Family Satisfaction, Service Quality, Outpatient Care